PENERAPAN SANKSI TERHADAP NARAPIDANA YANG MELANGGAR PASAL 4 HURUF (J) PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA NOMOR 6 TAHUN 2013 TENTANG TATA TERTIB LEMBAGA PEMASYARAKATAN DAN RUMAH TAHANAN NEGARA DI LEMBAGA PEMASYARAKATAN KLAS II B BANGKINANG - Nur Fajri; Erdianto '; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
On April 27, 1964, before the Indonesian prison house was converted to a penitentiary in accordance with the idea of Sahardjo, who was then justice minister. In prison systems, prisoners and prison students are entitled to physical education and guarantees of their rights to observe their worship, to engage with outsiders, whether family or other parties. Obtain information both through print and electronic media, and obtain a proper education. The purpose of writing this thesis include: first, to determine the role of Class II Penitentiary B Bangkinang in maintaining security to prevent inmates bringing mobile phones (hp) to Penitentiary. Secondly, to know the application of sanctions for inmates violating Article 4 letter (j) of the Ministerial Regulation and Human Rights on the Procedures of Penitentiary of Penitentiary and House of Detention. Third, to know the relation between Article 4 Letter (j) of the Regulation of the Minister of Law and Human Rights on the Procedures of Penitentiary of Penitentiary and House of Detainees with the principle of socialization.From the results of research problems there are three main things that can be concluded. First, the role of Class II Bang B Correctional Institution in maintaining security to prevent prisoners from bringing mobile phones to Penitentiary has not been implemented maximally. Proven from the security system that is run is still far from the word "safe" because there are still many inmates who can save and use goods that are prohibited to be brought into prisons Class II B Bangkinang. Secondly, Prison Officers have sought to impose sanctions on prisoners who commit violations in accordance with applicable regulations. However, there are still officers who are unfair persons in giving sanctions to prisoners who also commit violations but not processed and not sanctioned in accordance with Ministerial Regulation and Human Rights No. 6 of 2013 on the Standing Orders of Penitentiary and Detention Center of the State. Third, basically in prisons class II B Bangkinang has provided a special telephone shop (wartelsus) for inmates to contact family and relatives. If you want to communicate with family and so on can use wartelsus that has been provided by Class II Bang Bang Bang.Keywords: Prisoners-Violation-Sanctions